Foraging activities of stingless bees, Geniotrigona thoracica and Heterotrigona itama (Apidae: Meliponini) in relation to wet and dry seasons in Selangor, Malaysia - Wan Nur Asiah Wan Mohd Adnan,; Syari Jamian,; Nur Azura Adam,; Mohamad Shukri Tan Shilan,; Siti Asma Samsudin,; Chong, Leong Puan (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
This study reports the influence of wet and dry seasons on foraging activities of Geniotrigona thoracica and Heterotrigona itama in tropical climate of Malaysia. Foraging activities of the two bee species were recorded monthly from September 2014 to August 2015. Two methods of monitoring and counting the activities of the two species of stingless bees, (1) bees hovering in and bees hovering out (FIFO), and (2) bees collecting the pollen and bees bringing the nectar to their nest were recorded using a hand manual counter about 1 m2 from the nest entrance of each species studied. This study showed the wet season recorded the highest foraging activities for both species, with G. thoracica and H. itama incurred the highest number of flights in (FI) in January 2015 (FI G. thoracica = 12,303 individuals: FI H. itama = 12,011 individuals). This study also showed the lowest foraging activities for both species in dry season with the lowest number of flights in (FI) recorded for G. thoracica observed in September 2014 (4880 individuals) while H. itama showed in May 2015 (2168 individuals). Thus, the foraging activities of these bees might be affected by other environmental aspects such as the composition of flora species surrounding the stingless bee meliponiculture.